From energy security to security of energy eervices: The role of gendered innovations in living labs - Batinge, B.; Musango, J.K.; Ceschin, F.; Ambole, A.; Smit, S.; Mukama, M.; Petrulaityte, A. (South African Journal of Industrial Engineering, 2022)
Energy security remains a concern in Sub-Saharan Africa. The conceptualisation of energy security at the urban household level has shifted from the security of energy supply to the security of energy services, which is focused more on the demand side. Women and young girls are affected the most by insecure energy services. However, energy policy discourses often fail to focus on the security of energy services or to recognise gender roles in the provision of energy services at the household level. It is therefore imperative to develop innovative and gender-sensitive energy services solutions with a new paradigm of participatory solution design, such as living labs. We assessed living labs and the energy security landscape in poor urban environments through a systematic literature review, and proposed a framework for demonstrating how living labs could be used as a lever to promote the security of energy services. The security of energy services in poor urban households could be improved by harnessing the different innovative strengths of the respective genders. Living labs provide an ideal space for co-generating, co-designing, and co-learning to produce tailored energy services solutions. There is a need for a collaborative effort in resourcing researchers to undertake practical investigations of interactive multi-stakeholder platforms with those who are intended to benefit from the policy to increase its impact and to bridge the science-policy divide. © 2022, South African Institute of Industrial Engineering. All rights reserved.
Keywords: accès à l'électricité; afrique; afrique subsaharienne; approches et analyses; droits des femmes*; environnement; inégalités; patriarcat; projet charge mentale; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

La vulnérabilité face aux changements climatiques - Gagnon-Bouchard, Laurie (Spirale, 2022)
https://www.erudit.org/fr/revues/spirale/2022-n278-spirale06800/97844ac/
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; cours; environnement; fem3600; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; écoféminisme

Ville féministe : notes de terrain - Kern, Leslie (Les éditions du remue-ménage, 2022)
À qui appartient la ville? Sûrement pas aux femmes. Souvent le théâtre des violences ordinaires ou frontales, la ville repose sur des fondations sexistes. Kern s'attarde à la manière dont les relations de genre, de classe, de race, d'âge se déploient dans la ville. Elle nous invite à redéfinir et à nous réapproprier les espaces urbains. Comment rendre nos villes plus féministes? Partant de son expérience quotidienne de citadine à différentes époques de sa vie (enfant, adolescente, étudiante, travailleuse, militante et mère), elle s'appuie sur les théories d'urbanisme, des travaux de géographes féministes et des références à la culture pop pour montrer comment une ville genrée qui s'embourgeoise exclut les populations marginalisées, mais également pour évoquer les possibles configurations d'une ville plus inclusive.
Keywords: approches et analyses; cours; design; discipline; environnement; fem1250; inégalités; premier cycle; racisme; ressource en ligne; sexisme; systèmes d'oppressions; thématiques; urbanisation; urbanisme; violences

Gender, climate breakdown and resistance: The future of human rights in the shadow of authoritarianism - Rosamond, Annika B.; Davitti, Daria (Nordic Journal of Human Rights, 2022)
In this article we examine the future of human rights by looking at how ‘authoritarianism’, in its multifaceted forms and manifestations, intersects with existing discourses on climate change, environmental protection, populism and ‘gender deviance’. By adopting an intersectional lens, we interrogate the emergence of the right to a healthy environment and reflect on whether it will help against the double challenge faced by human rights: of climate breakdown and rising authoritarianism. We study the link between authoritarianism and populism, focusing on far-right populism and the creeping authoritarian features that we can associate with far-right groups, both movements and parties. We also consider how certain understandings of nature and the environment are put forward by authoritarian regimes. This leads us to consider so-called ‘ecologism’ and the ways in which far-right movements draw upon green thought on the natural environment to further a gendered agenda based on conceptions of nature as a ‘national treasure’. These conceptions, as we demonstrate, go hand in hand with policies that promote national identity and directly undermine the rights of migrants, ethnic minorities, women and LGBT+ groups. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; capitalisme; changements climatiques; discipline; droits des femmes*; droits humains; environnement; histoire et politique; intersectionnalité; patriarcat; populisme de droite; projet charge mentale; périodes historiques; racisme; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques; écologisme d'extrême-droite

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

Dead white men vs. Greta Thunberg: Nationalism, misogyny, and climate change denial in swedish far-right digital eedia - Vowles, Kjell; Hultman, Martin (Australian Feminist Studies, 2021)
In the autumn of 2018 Greta Thunberg started her school strike. Soon she and the Fridays For Future-movement rose to world-fame, stirring a backlash laying bare the intrinsic climate change denial of Swedish far-right digital media. These outlets had previously been almost silent on climate change, but in 2019, four of the ten most read articles on the site Samhällsnytt were about Thunberg, all of them discrediting the movement and spreading doubt about climate science. Using the conceptualisation of industrial/breadwinner masculinities as developed by Hultman and Pulé [2018. Ecological Masculinities: Theoretical Foundations and Practical Guidance. Routledge Studies in Gender and Environments. New York: Routledge], this article analyses what provoked this reaction. It explores how the hostility to Thunberg was constructed in far-right media discourse in the years 2018–2019, when she became a threat to an imagined industrial, homogenic and patriarchal community. Using conspiracy theories and historical tropes of irrational femininity, the far right was trying to protect the usually hidden environmental privileges, related to unequal carbon emissions and resource use, that Thunberg and her movement made visible. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discous dominant; environnement; europe; extrême-droite; histoire et politique; misogynie; médias; patriarcat; projet charge mentale; périodes historiques; régions géographiques; sexisme; stéréotypes de genre; suède; systèmes d'oppressions; thématiques; violences

Écoresponsabilité : la nouvelle « charge morale » des femmes - Lemelin, Silvie (2020)
Apparu dans les années 1980, le concept de charge mentale a été popularisé et brillamment illustré par Emma dans sa désormais célèbre bande dessinée Fallait demander [1]. La charge mentale, c’est la charge cognitive invisible que représentent la planification, l’organisation et la gestion de tout ce qui se situe dans la sphère domestique (tâches ménagères, rendez-vous, achats, soins aux enfants, etc.) et qui, chez les couples hétérosexuels[2], échoit généralement aux femmes en plus de leur activité professionnelle. Car les hommes, consciemment ou pas, désignent souvent leur compagne comme la responsable en titre de la logistique familiale. Et ce travail invisible prend énormément de temps et d’énergie psychique ; il génère davantage de stress que l’accomplissement des tâches domestiques comme telles, la charge mentale accompagnant les femmes au boulot et dans toutes leurs activités.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; amériques; approches et analyses; care; charge mentale; environnement; hétérosexisme; inégalités; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; travail invisible

Surviving the grind: how young black women negotiate physical and emotional labor in urban space - McCurn, Alexis S. (Sociological Spectrum, 2020)
This study draws on nearly 2 years of field research in Central East Oakland, CA, to provide an ethnographic account of the daily experiences of poor, young, black women in urban space. Few scholars have explored the collective experiences of young women living in the inner-city and the innovative strategies they develop to navigate daily life in this setting. The accounts from young women in this study reveal the different types of formal and informal labor black women do to ensure survival in the inner-city and how they describe this daily work as the “grind.” The intersection of formal and informal labor that makes up the grind is reflected in three dimensions: the half-time hustle, underground entrepreneurship, and informal support networks. Like men in the neighborhood women must contend with underemployment, poverty and race and class isolation. I explain how black women are impacted in very specific ways by these key structural shifts and harsh structural conditions and must in turn manage constraining and contradictory gendered expectations while negotiating the grind. © 2020, © 2020 Taylor & Francis Group, LLC.
Number: 4
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; capitalisme; environnement; intersectionnalité; milieu urbain; projet charge mentale; périodes historiques; racisme; régions géographiques; sexisme; stratégie de survie; systèmes d'oppressions; thématiques; travail; états-unis

Dénoncer les féminicides des femmes autochtones aux États-Unis et au Canada La bande dessinée Deer Woman d’Elizabeth LaPensée, une super-héroïne autochtone éco-féministe ? - Bonadè, Sophie; Hamus-Vallée, Réjane; Journée-Duez, Aurélie (Genre en séries, 2019)
À travers l’analyse de la bande dessinée Deer Woman créée en 2015 par Elizabeth LaPensée (Anishinaabe, Canada), notre article a pour objectif principal d’interroger la notion de « super-héroïne » à l’aune de représentations autochtones engagées. Il s’agit de voir en quoi cette revitalisation du mythe traditionnel de la Femme Cerf (Deer Woman) interroge l’identité en termes de sexe et de genre, la culture et la place des femmes autochtones, en prenant une position radicale face au problème sociétal des féminicides en Amérique du Nord. Nous postulons que la figure de Deer Woman peut aussi être vue aujourd’hui comme une allégorie mettant en garde contre la domination masculine sur les femmes et sur toutes autres formes de vie. Tout d’abord, nous étudierons les caractéristiques formelles de Deer Woman et les mythes fondateurs autochtones qui en sont à l’origine. Nous montrerons ensuite en quoi cette super-héroïne dont les pouvoirs apparaissent après qu’elle a été sexuellement agressée, tend à dénoncer et lutter contre les féminicides touchant les femmes autochtones. Enfin, nous nous demanderons comment cette bande dessinée pourrait laisser entrevoir l’émergence d’une super-héroïne autochtone éco-féministe.
Keywords: amérique du nord; amériques; approches et analyses; arts; bande-dessinée; cours; discipline; environnement; féminicide; féminisme autochtone; féminisme pop; histoire et politique; justice sociale; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; super-héroïnes; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Climate change, colonialism, and women’s well-being in Canada: What is to be done? - Williams, Lewis (Canadian Journal of Public Health, 2018)
The impacts of accelerating climate change across Canada are unequally distributed between populations and regions. Emerging evidence shows climate change and resultant policies to be worsening gendered social and economic inequities between women and men, with women’s participation largely absent in climate change research and decision-making. These dynamics are resulting in negative impacts for women’s well-being, with Indigenous and historically marginalized women at increased risk of experiencing health inequities as a result of climate change. To date, public health discourse has largely failed to incorporate gender as a key determinant of health in discussions of climate change impacts on populations. Paralleling this lack of development, the entangled relationship between climate and colonialism tends to be subsumed under the term “Aboriginality” within health determinants discourse. This commentary on gender and climate change in Canada is framed within a radical intersectional approach as an alternative course of public health analysis and action aimed at addressing resulting health and power inequities. Following an overview of evidence regarding the gendered impacts of climate change on women’s work, roles, agency, and well-being, several possible public health action areas on climate change and gender are highlighted as necessary components for resilient communities capable of meeting contemporary challenges.
Keywords: amériques; approches et analyses; canada; changements climatiques; environnement; intersectionnalité; invisibilisation des femmes autochtones; projet charge mentale; régions géographiques; santé; santé des femmes*; sexisme; système colonial; systèmes d'oppressions; thématiques

Emma - Emma (Emma, 2017)
Politique, trucs pour réfléchir et intermèdes ludiques
Keywords: 2000 à aujourd'hui; anticapitalisme; approches et analyses; bande-dessinée; charge mentale; charge émotionnelle; environnement; humour; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; travail invisible; violences; violences policières

Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Section: 1 volume (unpaged) : chiefly illustrations (some color) ; 26 cm
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Gender differentials and old age survival in the Nairobi slums, Kenya - Bennett, Rachel; Chepngeno-Langat, Gloria; Evandrou, Maria; Falkingham, Jane (Social Science & Medicine, 2016)
This paper examines gender differentials in survival amongst older people (50+ years) in the Nairobi slums and to the best of our knowledge is the first study of its kind in an urban African setting. The results provide evidence contrary to the expected paradox of poorer self-rated health yet better survival amongst older women. Older women in the Nairobi slums have poorer self-rated health and poorer circumstances across other factors, including disability and socio-economic status. Further, older women in the slums do not have better survival. The conventional female advantage in mortality only becomes apparent after accounting for the cumulative influence of individual characteristics, social networks, health and socio-economic status, suggesting the female advantage in unadjusted old-age mortality does not apply to contexts where women experience significant disadvantage across multiple life domains. This highlights the urgent need to redress the support, status and opportunities available for women across the life course in contexts such as the Nairobi slums. In addition, a greater number of factors differentiate mortality risk amongst men than amongst women, suggesting inequality amongst slum dwelling older men and highlighting the need for gender sensitive interventions which account for the particular needs of both genders in old age.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; bidonvilles; environnement; inégalités; kenya; personnes âgées; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power–in the form of economic, social, symbolic, and cultural capital–is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis

Plan Nord - Où sont les femmes autochtones ? - Arnaud, Aurélie (Recherches amérindiennes au Québec, 2011)
Parmi les sujets absents du débat sur les impacts et les conséquences du Plan Nord se trouvent, invisibles, les femmes autochtones. Celles qui constituent plus de 50 % de la population autochtone dans le Nord sont les moins écoutées, les moins consultées, les plus vulnérables. La question est absente et il y a peu de données disponibles quant à l’impact des activités minières ou des chantiers hydroélectriques sur la condition des femmes. Or, l’expérience de Femmes autochtones du Québec révèle que ce type de développement a souvent des incidences négatives sur la situation des femmes autochtones dans les communautés en exacerbant les préjugés, les violences et les inégalités. Pour poser la réalité des femmes autochtones dans et hors réserve, il faut préciser qu’en 2001, les femmes autochtones enregistraient un taux de monoparentalité deux fois plus élevé que celui des femmes non autochtones (19 % contre 8 %). Les nombreuses familles dirigées par des femmes autochtones sont donc plus dépendantes de l’aide sociale que les hommes autochtones le sont.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; inégalités; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

L'association des femmes inuites du Nunavik Saturviit : porteuses d'espoir et de paix - Koperqualuk, Lisa Q. (2008)
La revue est disponible gratuitement à cette adresse: https://numerique.banq.qc.ca/patrimoine/details/52327/21235?docref=7WwAmupy7jFapVusT6o59A
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; environnement; famille; féminisme autochtone; inégalités; maternité; nunavik; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; violences

The scientific revolution and the death of nature - Merchant, Carolyn (Isis, 2006)
The Death of Nature: Women, Ecology, and the Scientific Revolution, published in 1980, presented a view of the Scientific Revolution that challenged the hegemony of mechanistic science as a marker of progress. It argued that seventeenth-century science could be implicated in the ecological crisis, the domination of nature, and the devaluation of women in the production of scientific knowledge. This essay offers a twenty-five-year retrospective of the book’s contributions to ecofeminism, environmental history, and reassessments of the Scientific Revolution. It also responds to challenges to the argument that Francis Bacon’s rhetoric legitimated the control of nature. Although Bacon did not use terms such as “the torture of nature,” his followers, with some justification, interpreted his rhetoric in that light.
https://nature.berkeley.edu/departments/espm/env-hist/articles/84.pdf
Keywords: approches et analyses; capitalisme; discipline; environnement; projet charge mentale; santé; santé de la nature; sciences; sciences de l'environnement; sexisme; systèmes d'oppressions; thématiques; torture de la nature; violences; écoféminisme

« Des femmes et de la territorialité » Début d’un dialogue sur la nature sexuée des droits des autochtones - Woudenberg, Gerdine Van; Lapierre, Christine (Recherches amérindiennes au Québec, 2004)
Cet article, qui se situe dans l’ensemble des discours sur les droits des autochtones, explore de façon spécifique le sujet du rapport des femmes à la territorialité. En utilisant comme étude de cas les cultures wabanakies de la côte Est, l’auteure réexamine de manière critique les documents historiques pour analyser le rapport des femmes au « lieu » à travers leur relation à leur environnement et elle étudie comment le contexte de cette relation a été transformé par les processus de colonisation. Puisque ce texte s’insère dans le large champ des discours sur les droits autochtones, il soulève des questions importantes sur la position des femmes autochtones dans les processus actuels de reconnaissance des droits et des titres, non seulement comme participantes actuelles mais aussi comme acteurs historiques.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; environnement; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; territoire; thématiques; wabanakie

Policing the national body: Sex, race, and criminalization - Silliman, Jael Miriam; Bhattacharjee, Anannya; Davis, Angela Y.; Committee on Women, Population, and the Environment (South End Press, 2002)
Keywords: amériques; approches et analyses; corps; environnement; justice reproductive; maternité; nationalisme; racisme; régions géographiques; santé; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis